PERAN PENDIDIKAN AGAMA ISLAM DALAM PENGEMBANGAN KARAKTER SISWA DI ERA DIGITAL: TANTANGAN DAN PELUANG - Dede Pitri; Somad, Momod Abdul; Firmansyah, Mokh. Iman (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2025)
Islamic Religious Education (PAI) plays a strategic role in character development among students in the digital era, aiming to cultivate individuals with faith, piety, and noble character. This study explores the challenges and opportunities associated with integrating PAI into the digital era, highlighting issues such as the negative influence of social media, and lack of student focus. Utilizing a qualitative phenomenological approach, data were collected through interviews, and observations to gain insights into experiences and perceptions related to PAI in character building. The findings indicate that while technology can distract students, it also provides opportunities to enhance moral education through interactive digital tools, project-based learning, and the integration of Islamic values. Teachers’ proactive roles and collaboration with families and communities are essential in ensuring the effective implementation of PAI. The study concludes that adapting PAI with holistic strategies, combining technological integration and moral education, is crucial for fostering students' character in line with Islamic values.